2019
DOI: 10.3389/fnhum.2019.00403
|View full text |Cite
|
Sign up to set email alerts
|

Gender Difference in Gender Bias: Transcranial Direct Current Stimulation Reduces Male’s Gender Stereotypes

Abstract: Stereotypes exist in the interactions between different social groups, and gender stereotypes are particularly prevalent. Previous studies have suggested that the medial prefrontal cortex (mPFC) is involved in the social cognition that plays an important role in gender stereotypes, but the specific causal effect of the mPFC remains controversial. In this study, we aimed to use transcranial direct current stimulation (tDCS) to identify a direct link between the mPFC and gender bias. Implicit stereotypes were me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 56 publications
1
10
0
Order By: Relevance
“…A significant gender difference in the correlation between perceptions of sexism and brain activation also emerged, which supported our hypothesis. This aligns with previous studies indicating greater gender stereotypical bias in males (e.g., [ 66 , 72 ]). The results indicate that there was a stronger negative correlation in the female group compared to the male group, suggesting that greater perceptions of sexism were associated with reduced activity in the right cluster for the female group but not for the male group.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…A significant gender difference in the correlation between perceptions of sexism and brain activation also emerged, which supported our hypothesis. This aligns with previous studies indicating greater gender stereotypical bias in males (e.g., [ 66 , 72 ]). The results indicate that there was a stronger negative correlation in the female group compared to the male group, suggesting that greater perceptions of sexism were associated with reduced activity in the right cluster for the female group but not for the male group.…”
Section: Discussionsupporting
confidence: 92%
“…One transcranial magnetic stimulation (TMS) study found that the application of TMS to the left dlPFC and the right anterior dorsomedial PFC resulted in increased gender stereotypical bias in male participants compared to the application of TMS to a control site but not for female participants [ 71 ]. Similarly, a transcranial direct current stimulation (tDCS) study found that the application of anodal tDCS to the mPFC led to a significant reduction in the implicit gender stereotypes amongst male participants but not female participants [ 72 ]. Hence, the present study aimed to investigate gender differences in the neural correlates of self-referential gender stereotypes and the association with perceptions of sexism in the context of sexist-related comments.…”
Section: Introductionmentioning
confidence: 99%
“…Four articles tested the associations between explicit HS and BS (measured by the ASI) and related implicit measures. In general, the findings show that explicit HS and BS are related to implicit sexism (Laux et al, 2015) and implicit gender stereotyping (Ramos et al, 2016; Wang et al, 2019; Ye & Gawronski, 2018), but not always; some results differed 15 . Two other articles reported associations in men between HS and BS and the corresponding sexist behavior, which could be broadly defined as stereotype-consistent behavior 16 .…”
Section: Resultsmentioning
confidence: 81%
“…Another study found differential improvement in performance of verbal working memory between females and males, following tDCS (Meiron and Lavidor, 2013). Similarly, multiple studies reported that the observed tDCS induced augmentation of cognitive behaviour were gender dependent (Gao et al, 2018;Keshvari et al, 2013;Yang et al, 2018;Bertossi et al, 2017;Wang et al, 2019). Recently, a computational study reported gender related differences in the tDCS induced peak intensity of current at a target region of interest in the cortex.…”
Section: Gender Related Differences In Tdcs Effectsmentioning
confidence: 92%